Lower incidence of cytomegalovirus infection with everolimus versus mycophenolate mofetil in de novo cardiac transplant recipients: a randomized, multicenter study - Viganò, Mario; Dengler, Thomas; Mattei, M. F..; Poncelet, A.; Vanhaecke, J.; Vermes, E.; Kleinloog, R.; Li, Y.; Gezahegen, Y.; Delgado, J. F. (Transplant infectious disease, 2010)
Cytomegalovirus (CMV) is a major cause of infectious complications following cardiac transplantation, severely affecting short- and long-term outcomes. A 12-month, multicenter, randomized, open-label study in de novo cardiac transplant patients was undertaken to compare the efficacy, renal function, and safety of everolimus plus reduced cyclosporine versus mycophenolate mofetil (MMF) plus standard cyclosporine (ClinicalTrials.gov NCT00150046).
Gesehen am 05.09.2023